GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 43 species occurrences available in GBIF matching the query: TaxonKey: 3489565. The dataset includes 43 records from 16 constituent datasets: 1 records from Biological and palaeontological collection and observation data MNHNL. 4 records from New Zealand Fungal and Plant Disease Collection (PDD). 1 records from Registros de hongos en áreas protegidas de la Argentina. 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from Données ONF Faune-Flore-FOnge. 8 records from New Zealand Biodiversity Recording Network. 5 records from Danish Mycological Society, fungal records database. 1 records from Fungus herbarium, UiB. 1 records from Staffordshire Ecological Record - SER Species-based Surveys. 1 records from Artdata. 1 records from Donnees ONF Faune-Flore-Fonge. 2 records from Estonian University of Life Sciences. 4 records from CABI Bioscience Fungus Collection. 1 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 9 records from Botany (UPS). 2 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection.
Keywords: GBIF; biodiversity; species occurrences